Factors Influencing in the Fraudulent Financial Reporting - Arifin, Muhammad Burhanudin; Prasetyo, Andrian Budi (Jurnal Dinamika Akuntansi, 2018)
Fraudulent practice in financial report has resulted in the decrease of reliablity in financial report, causing losses for investors and creditors. The population used in this study are all listed on the Indonesia Stock Exchange (BEI) throughout 2010-2016. The sampling method used is purposive sampling. The number of samples used is 52 companies, consisting of 26 fraud companies obtained from the database of sanctioned misstatement of financial reporting issued by OJK during 2010-2016 period and 26 non-fruad companies with the same size determined under OJK regulation No. POJK.04 about Statement of Registration in the Public Offering and Capital Addition by Granting Right of Priority Effect by Companies with Small Scale Assets or Companies with Medium Scale Assets. This study used logistic regression analysis to examine the research hypothesis. The results of this study indicate that financial leverage and asset composition ratio have positive effect on the possibility of fraudulent financial reporting. Meanwhile, the profitability, liquidity, capital turnover, and receivable turnover ratio have negative effect on the possibility of fraudulent financial reporting .